2016
DOI: 10.21123/bsj.2016.13.2.0298
|View full text |Cite
|
Sign up to set email alerts
|

Study of total Immunoglobulin E and Eosinophil count in allergic disease

Abstract: This study was conducted to isolate and identify killer yeast Hanseniaspora uvarum from dates vinegar and measurement the ability of this yeast to produce killer toxin. The antimicrobial activity of the concentrated supernatant containing partially purified concentrated killer toxin was also detected against several pathogenic bacteria and yeast species, which includes two types of yeast Rhodotorula mucilaginosa and Candida tropicalis and four human pathogenic bacteria Staphylococcus aureus, Escherichia coli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Several studies reported that higher count of eosinophils was present in patients with allergic asthma. The results of this study are confirmed by earlier published data [29]. The results of that study showed that the percentage of eosinophil in allergic asthma patients was higher in comparison to the control (4.37 ± 0.52 vs. 2.57 ± 0.86%).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies reported that higher count of eosinophils was present in patients with allergic asthma. The results of this study are confirmed by earlier published data [29]. The results of that study showed that the percentage of eosinophil in allergic asthma patients was higher in comparison to the control (4.37 ± 0.52 vs. 2.57 ± 0.86%).…”
Section: Discussionsupporting
confidence: 91%